2023
DOI: 10.3390/agriculture13040811
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Behavior in the Field of Organic Agriculture and Food Products during the COVID-19 Pandemic in the Czech Republic: Focus on a Comparison of Hyper-, Super- and Farmers’ Markets and Direct Purchases from Producers

Abstract: The aim of this paper is to assess Czech food consumers’ behavior when buying organic products during the COVID-19 pandemic, with an emphasis on the place of purchase of organic agriculture and food products—especially those purchases with the shortest logistics value chain, i.e., purchase at farmers’ markets, or directly from the producer—and a comparison with the current most common places of purchase of organic products in the Czech Republic, supermarkets and hypermarkets. Categorical data analysis methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Correlation analysis showed that age is statistically significantly and positively related to the variable SUM_agroatt_3_infofood (r = 0.10 ** p < 0.05), indicating that the older the respondents, the more likely they are to show an attitude towards agriculture and food that characterizes a deeper awareness of food problems, which is accompanied by a desire for deeper information about the political and economic aspects of food production. Similar findings were shown by Zamková et al [64]. The authors declared that, generally, younger respondents (under 25 year) are not too interested in topics related to food procurement, while interest increases with age and education level.…”
Section: Detection Of Basic Patterns Of Changes In Attitudes Toward A...supporting
confidence: 84%
“…Correlation analysis showed that age is statistically significantly and positively related to the variable SUM_agroatt_3_infofood (r = 0.10 ** p < 0.05), indicating that the older the respondents, the more likely they are to show an attitude towards agriculture and food that characterizes a deeper awareness of food problems, which is accompanied by a desire for deeper information about the political and economic aspects of food production. Similar findings were shown by Zamková et al [64]. The authors declared that, generally, younger respondents (under 25 year) are not too interested in topics related to food procurement, while interest increases with age and education level.…”
Section: Detection Of Basic Patterns Of Changes In Attitudes Toward A...supporting
confidence: 84%
“…The issue of gender preferences in the purchase of organic food is addressed in, e.g., [11,48,[52][53][54][55][56]. The issue of preferences for buying organic food according to education has been addressed by, e.g., [48,[52][53][54][57][58][59].…”
Section: Methodsmentioning
confidence: 99%
“…The issue of gender preferences in the purchase of organic food is addressed in, e.g., [11,48,[52][53][54][55][56]. The issue of preferences for buying organic food according to education has been addressed by, e.g., [48,[52][53][54][57][58][59]. The issue of preferences for buying organic food according to income has been addressed by, e.g., [48,53,54,[58][59][60][61].…”
Section: Methodsmentioning
confidence: 99%
“…Satisfying the specific needs of the consumer promotes innovation, using bioactive compounds [4], with low fat content [5], flour or flakes of Andean grains [6], even tubers such as orange-fleshed sweet potatoes [2]. The purchase of traditional products, as well as organic ones, is closely tied to consumer behavior linked to the place and quantity of purchase, motivated by optimization reasons, production planning, ecological interests, rural development and value chain considerations [7]. These factors are closely related to their quality, price, appearance, brand, availability and place of origin [8].…”
Section: Introductionmentioning
confidence: 99%